Analysis of Sports Tourism Development Potential in Southeast Aceh Regency: Analisis Potensi Pengembangan Pariwisata Olahraga di Kabupaten Aceh Tenggara - Afrizal; Nababan, Melfa Br (Universitas Muhammadiyah Sidoarjo, 2023)
Southeast Aceh Regency provides outstanding Natural Resources for the development of Sport tourism. In order to discover ideal sports for the development of sport tourism in Southeast Aceh Regency, it is necessary to evaluate which sports are suitable with the natural circumstances in Southeast Aceh Regency so that suitable sports may be obtained and practiced in Southeast Aceh Regency. This study aims to analyze suitable sport tourism to be undertaken in Southeast Aceh Regency, and to offer suggestions to the regional government of Southeast Aceh Regency regarding what sport tourism can be conducted or held in Southeast Aceh Regency to attract and increase tourist visitors to Southeast Aceh Regency. In addition, it serves local regional orders with suggestions for necessary matters for expanding and investigating tourism in the Southeast Aceh Regency. The descriptive approach including field survey data collection techniques, surveys, and interviews was employed. According to the research results, the recommended sports include Trail Running, Downhill Bicycles, Rafting, and Hiking. This sports offer the potential for sport tourism in line with the area's natural circumstances. With the recommendations for sport tourism, it is possible to generate regional economic income. Those sports will be able to develop into Southeast Aceh Regency's top sport accomplishments.